Tale of the heart queen ebook - Tuli, Nisha J. (Artefacts of Ouranos, 2024)
The epic fourth novel in the irresistibly sexy BookTok phenomenon . . . Some mistakes can’t be undone, and Lor now faces the crushing consequences of her wild, fae magic. She’s already set events in motion, and there’s no escaping the relentless pursuit of the Aurora King. Everyone wants something from her, and her list of enemies keeps growing, each more powerful—and vindictive—than the last. Lor is fighting for more than just her freedom. She’s fighting for her soulmate, her family, and for a chance to bring peace to Ouranos itself. But with every blast of her uncontrolled Heart magic, Lor risks not only the lives of those she loves, but making the same, doomed mistakes as her grandmother. Ones that ripped the very fabric of the kingdom apart. Lor has no choice but to follow the path before her. Because powerful forces now shape and shift her fate—and the Heart Queen now faces the ultimate test . . . if she’s ready.